Dampak Penerapan Program Pemberdayaan UMKM Kampung Madani PT. PNM Terhadap Peternak Sapi Perah: Penelitian - Nindya Rahma Aulya; Lilis Nurlina; M. Ali Mauludin (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to analyze the impact of the Kampung Madani MSME Empowerment Program implemented by PT. Permodalan Nasional Madani (PNM) on dairy cattle farmers in Cibodas Village, Lembang Subdistrict, West Bandung Regency. The program focuses on strengthening farmers’ capacities through training, mentoring, business clustering, and the processing of livestock waste into value-added products such as biogas, compost, and vermicompost. A qualitative case study approach was employed, with data collected via in-depth interviews, observation, documentation, and literature review. The results show that the implementation of the POAC (Planning, Organizing, Actuating, and Controlling) management functions in the program was relatively effective. This effectiveness is evident in the successful planning and organization of the worm cultivation activities carried out by the group, as well as in the structured execution and supervision processes. Social impacts include increased community participation, shifts in mindset toward sustainable farming, and strengthened social networks. Economic impacts are reflected in increased household income through waste utilization and reduced operational costs.